Penerapan Sanitasi dan Higienis dalam Pembuatan Jamu Gendong di Kota Tebing Tinggi - Suprianto, Suprianto; De Lux Putra, Effendy; Nurbaya, Siti; Samran, Samran; Sumardi, Sumardi; Nasution, Derlina; Lestari, Wita (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Jamu Gendong is a traditional drink that has the potential to be contaminated with worms, parasites, bacteria, fungi, viruses and rickettsia. Sources of contaminants include materials, equipment, facilities, personnel, animals and production environments, so their efficacy is questionable. The activity was carried out in the form of providing information on the implementation of sanitation and hygienic production to 38 Jamu Gendong traders in Tebing Tinggi City, Deli Serdang, North Sumatra. The material was delivered using illustrated power point media to facilitate the delivery of increased understanding of sanitation and hygiene, including objectives, benefits, programs, fixed procedures, disinfectant and washing materials as well as documentation in accordance with RI POM Regulation Number 31, 2022. Activities were carried out on April 29, 2024 and received positive responses from all participants. Activities are expected to be sustainable so that the Jamu Gendong produced is of higher quality.